2
$\begingroup$
  • For all real numbers it is true that $$ a^{8} - 1 = \left(a^{2} - 1\right)\left(a^{2} + 1\right) \left(a^{2} + \,\sqrt{\,2\,}\,a + 1\right) \left(a^{2} - \,\sqrt{\,2\,}\,a +1\right) $$ How do I arrive at this ?.
  • I started thinking that $a^{8} -1$ is the $3$rd binomial formula so that $a^{8} - 1 = \left(a^{4} + 1\right)\left(a^{4} - 1\right)$, but then it basically says "stop" in my mental sphere.

I'm preparing for an admissions exam please help !. THX.

$\endgroup$
2
$\begingroup$

\begin{align} (a^8-1) &= (a^4-1)(a^4+1) \\ &= (a^2-1)(a^2+1)(a^4+2a^2+1 - 2a^2) \\ &= (a^2-1)(a^2+1)((a^2+1)^2 - 2a^2) \\ &= (a^2-1)(a^2+1)((a^2+1) - \sqrt{2}a)((a^2+1) + \sqrt{2}a) \end{align}

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

HINT:

$$(a^2)^2+1=(a^2+1)^2-(\sqrt2a)^2=\cdots$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.